Increased Incidence of Resistant Hypertension in Patients With Systemic Lupus Erythematosus: A Retrospective Cohort Study. Issue 4 (27th March 2020) - Gandelman, Jocelyn S.; Khan, Omair A.; Shuey, Megan M.; Neal, Jacquelyn E.; McNeer, Elizabeth; Dickson, Alyson; Barnado, April; Wang, Li; Anandi, Prathima; Dupont, William D.; Stein, C. Michael; Chung, Cecilia P.
Abstract : Objective: To compare the risk of resistant hypertension (RHTN) in patients with systemic lupus erythematosus (SLE) and in controls without SLE, and to define factors associated with RHTN in patients with SLE. Methods: We studied 1, 044 patients with SLE and 5, 241 control subjects using de‐identified electronic health records from a tertiary care center. SLE was defined as ≥4 International Classification of Diseases, Ninth Revision codes for SLE and antinuclear antibody titer ≥1:160. RHTN was defined as uncontrolled blood pressure on 3 antihypertensive medications or requiring 4 or more antihypertensives to attain control. First, we compared the risk of RHTN between groups. Second, we examined the association between RHTN and all‐cause mortality in patients with SLE. Results: RHTN was nearly twice as prevalent in patients with SLE compared to control subjects (10.2% and 5.3%, respectively), with an incidence rate of 10.2 versus 6.1 cases per 1, 000 person‐years of observation (hazard ratio [HR] 1.72 [95% confidence interval 1.28–2.30]; P < 0.001, adjusted for age, sex, race, baseline end‐stage renal disease [ESRD], creatinine, and calendar year). In patients with SLE, we found associations between RHTN and black race, lower renal function, hypercholesterolemia, and increased inflammatory markers. RHTN was associated with a significantly higher mortality risk (HR 2.91, P = 0.0005) after adjustment for age, sex, race, calendar year, creatinine, baseline ESRD, and number of visits. Conclusion: Patients with SLE have a higher risk of RHTN compared to frequency‐matched controls, independent of multiple covariates. RHTN is an important comorbidity for clinicians to recognize in SLE, because it is associated with a higher risk of mortality.